Knowledge, attitude, and practice assessment toward COVID-19 among communities in East Nusa Tenggara, Indonesia: A cross-sectional study - Lee, Felix; Suryohusodo, Aileen Alessandra (Frontiers in Public Health, 2022)
Objective This research aimed to assess the knowledge, attitude and practice toward COVID-19 among East Nusa Tenggara (NTT) population and identify associated sociodemographic factors. Methods A cross-sectional study was performed among communities in 22 regencies of NTT between October–November 2021 using a structured and validated questionnaire that consists of 22-items of knowledge, 6-items of attitude and 13-items of practice related COVID-19 questions. A cut off point of at least 70% was employed to categorize good knowledge, attitude, and practice. Results The percentages of survey respondents showing good knowledge, attitude and practice toward COVID-19 were 79.8, 72.7, and 94.6%, respectively. There was a significant positive, though weak, linear correlation between knowledge and practice scores (ρ = 0.097; p = 0.049). Knowledge was strongly associated with regency of residence (Cramer's V = 0.266; p = 0.010), education (Cramer's V = 0.312; p < 0.001), and occupation (Cramer's V = 0.313; p < 0.001). Attitude and practice had strong relationship with regency of residence (Cramer's V = 0.289; p = 0.024) and education (Cramer's V = 0.272; p < 0.001), respectively. Conclusion Nearly all survey participants showed good precautionary behaviors, but there was still a quarter of respondents indicated poor knowledge and attitude. There was also a positive relationship between knowledge and practice scores thereby indicating the importance of local public health advocates to distribute information uniformly especially to the groups with inadequate knowledge toward COVID-19 as a means to control the virus transmission.